PERAN RELEGIUSITAS DALAM MEMODERASI KEPUTUSAN INDIVIDU DALAM MEMILIH SEKOLAH DASAR ISLAM TERPADU DI KARANGANYAR - Apriyana Nurwahyudi; Budi Haryanto (UNIVERSITAS PGRI MADIUN, 2018)
ABSTRACTThis research to analyze variables which influence parents to make decision to send their children go to Islamic Primary School of Integrated. It aims to determine the effect of price perception, perception of quality, the image on the decision of parents to send their children go to school with religiousity as moderating variable. Collecting data using a questionnaire survey method with convenience sampling technique. The research sample of 200 respondent are individuals who want to send their children go to Islamic Primary School of Integrated, This research was carried out by taking a sample in public area such as mall, market, and kindergarten school in Karanganyar. Results SEM analysis show that religiousity as moderating influences perception of the quality of teaching, image of school, and school fee when parents sent their children go to Islamic Primary School of Integrated, because people with high religiousity will consider with influences perception of the quality of teaching, image of school, while people with lower religiousity influenced by other variable outside the variable perception of the quality of teaching, image of school dan school fee.Keywords : Perception of price, quality of teaching, image, religiousity, decision.